A comparative study on conceptual-based and experiential-based learning of accounting information systems as evaluated by different measures of effectivity - Cai, Jasmin Alaine R. (Animo Repository, 2023)
As technology advances, the use of accounting information systems (AIS) and enterprise resource planning software (ERP) have become more apparent not only in businesses but also in education. The main purpose of this study was to be able to assess and compare conceptual-based learning and experiential-based learning of AIS through different measures of effectivity namely, learning methods, satisfaction, computer self-efficacy, and academic performance. The study aimed to identify whether there is a significant difference between the two learning approaches when it comes to learning AIS. The researchers conducted an online survey with a total of 386 respondents from universities and colleges based in Luzon. Qualified respondents were BSA students that had taken the course and were mainly divided into two groups—those who took the AIS course or its equivalent under conceptual-based learning and those who took the course with an integrated practical application of ERP software under an experiential-based learning approach. Primary data were gathered through online surveys which assessed the participant’s learning methods, satisfaction, computer self-efficacy, and academic performance. The data set was tested for normality using the Shapiro-Wilk Test and the Central Limit Theorem in which results showed that the data approached a normal distribution. The data from the online survey was then analyzed and compared through descriptive statistics, t-test, Pearson correlation, and Mann-Whitney U-Test using the SPSS software. Results showed that there was a significant difference between conceptual-based and experiential-based learning of AIS in terms of learning methods, satisfaction, computer self-efficacy, and academic performance. Thus, insightful recommendations were provided for those who may benefit from the results of this study.